Realidade Virtual Aplicada a Medicina: Simulador de Caminhada Para análise da Frequência Cardíaca - Diniz, Ivando S. (Anais da Escola Regional de Computação Aplicada à Saúde (ERCAS); 2018: Anais da VI Escola Regional de Computação aplicada à Saúde, 2018)
This article describes the virtual walking simulator for heart rate analysis. The system was developed in the UNREAL ENGINE 4 environment and consists of heart rate sensor and "Mini stepper". The system is connected to the computer and viewed through the monitor. The interface was made using the Arduino Atmega 2560 kit and RS232 serial communication. The simulator and heart rate sensor presented values for different environments.